A force reflection robust control scheme with online authority adjustment for dual user haptic system. (1st January 2020) - Motaharifar, Mohammad; Taghirad, Hamid D.
Highlights: A control scheme with online authority adjustment is developed for dual user haptic systems. The task dominance is automatically adjusted based on the task performance of the trainee with respect to the trainer. A robust controller is developed to satisfy the requirement of position tracking. The input-to-state stability (ISS) of the nonlinear closed loop system is analyzed. Experimental results demonstrate the effectiveness of the proposed control approach. Abstract: This article aims at developing a control structure with online authority adjustment for a dual-user haptic training system. In the considered system, the trainer and the trainee are given the facility to cooperatively conduct the surgical operation. The task dominance is automatically adjusted based on the task performance of the trainee with respect to the trainer. To that effect, the average norm of position error between the trainer and the trainee is calculated in a sliding window and the relative task dominance is assigned to the operators accordingly. Moreover, a robust controller is developed to satisfy the requirement of position tracking. The stability analysis based on the input-to-state stability (ISS) methodology is reported. Experimental results demonstrate the effectiveness of the proposed control approach.